Meningkatkan Status Gizi Anak Sekolah Dasar Melalui Permainan Edukasi: Belajar di Pedesaan Indonesia - Mufaiduddin, Muhammad; Sonda, Vanessa Julia; Azizah, Siti Nur; Agusman, Desi Destiana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Nutritional deficiencies in elementary school children in developing countries, including Indonesia, are still a major problem. One of the causes is the lack of knowledge and misperceptions in choosing healthy foods. To address this problem, we implemented a game-based nutrition education program to improve the knowledge of elementary school children in West Nusa Tenggara, Indonesia. This program involved 44 students in grades 5 and 6 of SD N 02 Gili Indah, Gili Trawangan, and was carried out on August 16, 2023 with the Semangat Muda Indonesia team. This activity consisted of two sessions: nutrition screening by measuring nutritional status and balanced nutrition education using posters. The results of the activity showed that 90.9% of children had normal nutritional status, while the other 9.1% had poor or poor nutritional status. Nutrition education through games and interactive discussions has proven effective in improving children's understanding of balanced nutrition. This can be seen from their correct responses in answering questions at the end of the session and their enthusiasm during the discussion. In conclusion, this game-based nutrition education approach is effective in improving the knowledge of elementary school children because the method is fun and can change their behavior.